SINDROM PICKWICKIAN-SINDROM HIPOVENTILASI PADA OBESITAS: LAPORAN KASUS DENGAN PENDEKATAN DIAGNOSIS KLINIS - Ni Luh Putu Dirasandhi Semedi Putri; Desak Ketut Indrasari Utami; I Gusti Ngurah Budiarsa; Sri Yenni Trisnawati (PERDOSNI, 2019)
OBESITY HYPOVENTILATION SYNDROME–THE PICKWICKIAN SYNDROME A CLINICALLY DIAGNOSTIC APPROACH CASE REPORTABSTRACTA 36-year-old man complained about snoring in the past 3 years with a very loud snoring interspersed with choking. This recurs throughout the night, thus, he often experiences excessive drowsiness during the day. He also experienced generalized tonic-clonic seizure in the past six months during sleeping at night or immediately after wake up in the morning. It happened three to four times a week. In the past one month he also experienced a morning headache. He was classified as morbid obesity and had 47.2 cm wide of neck circumference. STOP-BANG score and Snoring Severity Score (SSS) indicated high risk of Obstructive Sleep Apnea. Apnea Hypopnea Index (AHI) was 55.5. The Epworth Sleepiness Scale (ESS) score was 15 indicated to have an excessive sleepiness during the day. Blood gas analysis showed a hypercapnia and chronic hypoventilation condition characterized by the increasing of pCO2 and HCO3- with normal pH. A complete blood count examination showed polycythemia. The patient was diagnosed as Obesity Hypoventilation Syndrome (OHS) based on obesity, OSA, and chronic hypoventilation. With a limited gold standard diagnostic tools, such as polysomnography (PSG), a clinical approach using sleep tools and blood gas analysis to detect early stage OHS still can be made.Keywords: Chronic hypoventilation, morbid obesity, Obesity Hypoventilation Syndrome, obstructive sleep apneaABSTRAKSeorang laki-laki 36 tahun dikeluhkan selalu mendengkur sejak 3 tahun dengan suara dengkuran yang sangat keras diselingi tersedak. Hal ini berulang sepanjang malam hingga pasien sering mengantuk berlebihan di siang hari. Pasien juga mengalami bangkitan umum tonik klonik sejak enam bulan, saat sedang tidur malam hari atau segera setelah terbangun di pagi hari. Sejak 1 bulan, pasien mengeluh sakit kepala saat bangun pagi. Pasien tergolong morbid obesity dan lingkar leher 47,2cm. Skor STOP-BANG dan skor Snoring Severity Score (SSS) menunjukkan risiko tinggi obstructive sleep apneu (OSA), serta Apnea Hypopnea Index (AHI) adalah 55,5. Skor Epworth Sleepiness Scale (ESS) 15 menunjukkan mengantuk berlebihan di siang hari. Pemeriksaan analisis gas darah didapatkan kondisi hiperkapnia dan hipoventilasi kronik berupa peningkatan pCO2 dan HCO3- dengan pH darah cenderung normal. Pemeriksaan darah lengkap menunjukkan polisitemia. Pasien didiagnosis sebagai Sindrom Hipoventilasi pada Obesitas (SHO) karena adanya obesitas, OSA, dan hipoventilasi kronik. Meskipun memiliki keterbatasan alat diagnostik baku emas seperti polisomnografi (PSG), namun pendekatan klinis beserta sleep tools dan analisis gas darah dapat digunakan untuk mendeteksi dini SHO.Kata kunci: Hipoventilasi kronik, morbid obesity, Obesity Hypoventilation Syndrome, obstructive sleep apneu